Online Learning Features and Factors in Getting the Blend Right - (:unkn) unknown (My University, 2011)
This presentation discusses online learning provision using blended approach in educational settings. Online learning provision in the African setting includes both the traditional e-Learning management systems (e. g. proprietary – blackboard and webCT), and Open Source (i. e. Moodle, KEWL etc.). Online learning can feature at primary, junior and senior secondary as well as tertiary levels. However, within the African context, much emphasis is placed on the tertiary level and the scope of this paper focuses on eLearning provision within the tertiary level where it is believed that necessary resources are available. The paper firstly outlines the features of online learning, secondly outlines several factors that would determine the level and success of online provision in tertiary institutions in Africa; and lastly, discusses challenges and blended learning trends regarding online provision given the several factors in place.
Keywords: African Research